Exploring overlooked factors in seismic hazard evaluation of subduction zones: examples from the Himalaya - Hu, Wan-Lin (Nanyang Technological University, 2023)
Seismic hazard assessments rely on the available knowledge and constraints that can be applied, including various observations and a thorough understanding of regional structures and tectonics. However, these assessments are subject to various sources of uncertainty. These uncertainties may arise from incomplete knowledge, limited data resolution, or the use of simplified assumptions in standard frameworks for evaluating seismic hazards. This study primarily examines publications and quantifies the potential reduction of seismic moment caused by previously unconsidered structural effect–duplex structures at the depth of the Himalayan orogeny. This study also evaluates the uncertainty that may result from the subjective interpretation of seismic reflection images in the frontal Himalaya.